Harnessing the joint effect of approach bridges in arch bridge construction: an analytical study on thrust stiffness and elevation error mitigation - Wang, Shaorui; Feng, Ji; Yang, Ligui; Cai, Guoqing; Jiang, Daimin (Frontiers in Materials, 2024)
The horizontal component force of the backstay in arch bridge cable-stays is challenging to reach equilibrium completely, and the buckle tower stiffness significantly impacts the line shape of the main arch ring. The greater the buckle tower stiffness, the lower the construction difficulty. Therefore, this study proposed a method of enhancing the longitudinal thrust stiffness of the buckle tower using the joint effect of approach bridges. Sensitivity analysis was performed on the approach bridgecomposite buckle tower structure to derive the optimal combination method, establishing an analytical expression for the thrust stiffness of the approach bridge-composite buckle tower structure.This study used numerical analysis to explore the composition mechanism of the thrust stiffness influenced by pier-girder connection and discussed the applicability of the joint effect of approach bridges during the cantilever assembly process of arch ribs. Following conclusions were obtained: (1) Before the installation of the main girder of the approach bridge, given that the steel buckle tower and the junction pier have been consolidated, the optimal combination method is to form a "T" rigid structure by rigidly connecting the main girder of the approach bridge with the composite buckle tower, which has self-weight deflection and pier-girder rotation restriction effects; (2) The study presents analytical formulas for the completely rigid pier-girder connection of the approach bridgecomposite buckle tower structure, partially rigid pier-girder connection, and pre-deviation. Combined with the calculation program, this can guide structural design; (3) When a large downward elevation error of the arch ribs occurs in the middle and later stages, the cable force needed to install new arch segments becomes overly large. Therefore, the joint effect of approach bridges can be utilized to substitute for part of the cable force, which also minimizes potential elevation errors that could occur in subsequent arch ribs in the absence of this joint effect.